Forum ekspertówDevelopment and pharmacological characterization of a novel plasma-based in vitro angiogenesis assay - Jurasz, Paul; Santos-Martinez, Maria Jose; Radomska, Anna; Radomski, Marek W. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Background: In vitro angiogenesis assays were first described in the early 1980s, when it was found that endothelial cells form capillary-like structures (CLS) on matrices of collagen, laminin or fibrin. These assays have been useful in unravelling some of the molecular steps involved in angiogenesis, as well as in screening potential angiogenesis inhibitors. Aim: The aim of our current study was to develop a novel in vitro angiogenesis assay. Material and methods: A heat-coagulated plasma matrix was used as substrate for CLS formation by cultured human umbilical vein endothelial cells (HUVECs). Angiogenesis was quantified by counting CLS branch points and by the release of matrix metalloproteinase-2 (MMP-2) from HUVEC as measured by gelatin zymography. Results: In our current study, we demonstrate the formation of CLS, by HUVECs stimulated with phorbol-12 myristate-13 actetate (PMA), on a heat-coagulated plasma matrix. CLS formation was inhibited by the angiogenesis inhibitor angiostatin and by the matrix metalloproteinase inhibitor o-phenanthroline. Conclusions: Hence, we propose that this novel assay may be a useful tool to study angiogenesis in vitro and to screen possible pharmacological inhibitors of angiogenesis.